WOOD-POLYMER COMPOSITES BASED ON A MIXTURE OF RECYCLED POLYOLEFINS (Innovation in Woodworking Industry and Engineering design, 2026)
Polyolefins are among the most widely used polymers. This leads to accumulation of huge quantities of used mixed polymers, which can hardly be separated and reprocessed. Using a mixture of recycled polyolefins for preparing wood-polymer composites is one of theoptions for improving the properties and utilization of mixed polyolefin materials. The influence of modification of maleated polypropylene and SBR on the physical and mechanicalproperties of composites made from wood flour and recycled polyolefin.